2009
DOI: 10.1080/00952990802585406
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Reduction in Buprenorphine Injection After Introduction of Co-Formulated Buprenorphine/Naloxone to the Malaysian Market

Abstract: Background Diversion of buprenorphine (BPN) has been described in settings where it is legally prescribed and has resulted in increasing concern. To address this concern, co-formulation of buprenorphine/naloxone (BPN/NLX) replaced buprenorphine alone in Malaysia in December 2006. Methods To assess the significance of BPN/NLX introduction, 41 BPN/NLX injectors in Kuala Lumpur, Malaysia were recruited using a modified snowball recruitment technique. Results In January 2007, all subjects had previously inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 19 publications
0
50
1
Order By: Relevance
“…By the end of the treatment period, results were in favor of methadone 33 . However, these results need more investigation before they can be generalized 32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By the end of the treatment period, results were in favor of methadone 33 . However, these results need more investigation before they can be generalized 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The approach involves using µ-opioid agonists with long half-lives, such as buprenorphine and methadone that will reduce withdrawal symptoms and produce less drug-like effects. Up to the present time, there has been no evidence-based guidelines for the management of buprenorphine injection 32 . In a trial led in Iran by Ahmadi and Ahmadi K, 204 buprenorphine injectors were randomized to receive methadone(orally), buprenorphine (sublingually) or naltrexone, an opioid antagonist, (orally) along with counselling sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Malaysia that evaluated the continued IV use of BUP-N after the discontinuation of BUP reported that 98 % either injected the same amount or more after the change with only 2 % decreasing their injection [51]. In Finland, 68 % of respondents in a survey at a needle exchange clinic reported that they had tried injecting BUP-N; 45 % used it more than once, and 8 % used it regularly.…”
Section: Agonist/antagonistmentioning
confidence: 99%
“…Findings from a small sample (N=41) in Malaysia suggest that the introduction of the buprenorphine/naloxone combination did not decrease injection-related risk behaviors and was associated with increased benzodiazepine use [95]. A more systematic study in Malaysia, a two-wave survey of buprenorphine IDUs, found that both buprenorphine and buprenorphine/naloxone intravenous misuse occurred in heroin IDUs [60].…”
Section: Extent Of the Problem In The Us And Non-european Countriesmentioning
confidence: 99%